Musculoskeletal Biomarkers Response to Exercise in Older Adults - Abreu, Eduardo L.; Vance, Amy; Cheng, An-Lin; Brotto, Marco (Frontiers in Aging, 2022)
Exercise is an essential component of any good health style, being particularly important for older adults to counteract the effects of aging, including sarcopenia and osteoporosis, which can result in lower fall probability. Exercise programs for older adults are especially designed for that population. A rigorous evaluation of those programs is necessary to assure most benefit is achieved. Serum biomarkers of proteins intrinsic to musculoskeletal homeostasis could contribute objectively to the assessment of the benefits of exercise. In this work, in addition to the usual physical fitness and balance tests, ELISA assays quantified the serum levels of six proteins and one polysaccharide important for the homeostasis of muscle (Troponin T and alpha-Actin), tendon/ligament (Tenomodulin), cartilage (Cartilage Oligomeric Matric Protein and Hyaluronan) and bone (Osteocalcin and Sclerostin), before and after eight weeks of an exercise program tailored to older adults, Stay Strong Stay Healthy, offered at a Community Center and at an Independent Senior Living facility. Statistical significance was determined by non-parametric tests (Wilcoxon Signed Ranks and Mann-Whitney U). Physical fitness and balance improved as expected along with a significant decrease in Sclerostin, pointing to less inhibition of bone deposition. However, when considering each type of dwelling separately, older adults always saw a significant decrease of the isoform of Troponin T associated with fast-twitch muscles, suggesting that daily levels of physical activity may also have a role in the benefit of older adults from exercise.